Test Case Co-Migration Method Patterns - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Software Engineering 2020 Workshopband)

On the Development of Context-aware Augmented Reality Applications - Yigitbas, Enes; Jovanovikj, Ivan; Sauer, Stefan; Engels, Gregor (Handling Security, Usability, User Experience and Reliability in User-Centered Development Processes - IFIP WG 13.2/13.5)

Validating Test Case Migration via Mutation Analysis - Jovanovikj, Ivan; Nagaraj, Achyuth; Yigitbas, Enes; Anjorin, Anthony; Sauer, Stefan; Engels, Gregor (Proceedings of the 1st IEEE/ACM International Conference on Automation of Software Test AST)

Development Framework for Context-Aware Augmented Reality Applications - Krings, Sarah Claudia; Yigitbas, Enes; Jovanovikj, Ivan; Sauer, Stefan; Engels, Gregor (Proceedings of the 12th ACM SIGCHI Symposium on Engineering Interactive Computing Systems (EICS 2020))

Integrated Model-driven Development of Self-adaptive User Interfaces - Yigitbas, Enes; Jovanovikj, Ivan; Biermeier, Kai; Sauer, Stefan; Engels, Gregor (International Journal on Software and Systems Modeling (SoSyM))

Component-Based Development of Adaptive User Interfaces - Yigitbas, Enes; Josifovska, Klementina; Jovanovikj, Ivan; Kalinci, Ferhat; Anjorin, Anthony; Engels, Gregor (Proceedings of the 11th ACM SIGCHI Symposium on Engineering Interactive Computing Systems (EICS 2019))

Process Weakness Patterns for the Identification of Digitalization Potentials in Business Processes - Rittmeier, Florian; Engels, Gregor; Teetz, Alexander (Business Process Management Workshops)

WindCORES - Digital Transformation with Renewable Energy - Yigitbas, Enes; Schomaker, Gunnar (International Tube Association (ITAtube) Journal)

Detection and Resolution of Data-Flow Differences in Business Process Models - Jovanovikj, Ivan; Yigitbas, Enes; Gerth, Christian; Sauer, Stefan; Engels, Gregor (Information Systems Engineering in Responsible Information Systems - CAiSE Forum 2019, Rome, Italy, June 3-7, 2019, Proceedings)

Modular Construction of Context-Specific Test Case Migration Methods - Jovanovikj, Ivan; Yigitbas, Enes; Grieger, Marvin; Sauer, Stefan; Engels, Gregor (Proceedings of the 7th International Conference on Model-Driven Engineering and Software Development - Volume 1: MODELSWARD,)

Consistent Runtime Adaptation of User Interfaces - Anjorin, Anthony; Yigitbas, Enes; Kaindl, Hermann (Proceedings of the 8th International Workshop on Bidirectional Transformations (Bx 2019))

Towards Model-based Development of Context-aware Augmented Reality Applications - Yigitbas, Enes; Jovanovikj, Ivan; Sauer, Stefan; Engels, Gregor (Softwaretechnik-Trends, Proceedings of the 21st Workshop Software-Reengineering & Evolution (WSRE) & 10th Workshop Design for Future (DFF))

Context- and Data-driven Satisfaction Analysis of User Interface Adaptations Based on Instant User Feedback - Yigitbas, Enes; Hottung, André; Mansfield Rojas, Sebastian; Anjorin, Anthony; Sauer, Stefan; Engels, Gregor (Proceedings of the ACM on Human-Computer Interaction)

On-the-fly Usability Evaluation of Mobile Adaptive UIs through Instant User Feedback - Yigitbas, Enes; Jovanovikj, Ivan; Josifovska, Klementina; Sauer, Stefan; Engels, Gregor (Proceedings of the 17th IFIP TC.13 International Conference on Human-Computer Interaction (INTERACT 2019))

A Context-aware Virtual Reality First Aid Training Application - Yigitbas, Enes; Heindörfer, Joshua; Engels, Gregor (Proceedings of the Mensch und Computer 2019 (MuC ’19))

A Model-based Framework for Context-aware Augmented Reality Applications - Yigitbas, Enes; Jovanovikj, Ivan; Sauer, Stefan; Engels, Gregor (Handling Security, Usability, User Experience and Reliability in User-Centered Development Processes (IFIP WG 13.2 & WG 13.5 International Workshop @ INTERACT2019))

ABIS 2019 – 23rd International Workshop on Personalization and Recommendation on the Web and Beyond - Augstein, Mirjam; Herder, Eelco; Wörndl, Wolfgang; Yigitbas, Enes (30th ACM Conference on Hypertext and Social Media (HT ’19), September 17–20, 2019, Hof, Germany)

Model-Driven Engineering of Self-Adaptive User Interfaces - Yigitbas, Enes

Projektmanagement und Vorgehensmodelle 2019. Neue Vorgehensmodelle in Projekten – Führung, Kulturen und Infrastrukturen im Wandel.

Partizipation von Beschäftigten in der Gestaltung einer digitalisierten Arbeitswelt 4.0 mittels einer Canvas-Methode - Fischer, Holger Gerhard; Rittmeier, Florian; Strothmann, Thim Frederik; Schwenniger, Nina (Arbeit 4.0 im Mittelstand)
Sinnvolle und gebrauchstaugliche digitale Assistenzsysteme, die Beschäftigte bei ihren alltäglichen Aufgaben unterstützen, stellen eine Herausforderung für viele Organisationen hinsichtlich der individuellen und organisationalen Akzeptanz einschließlich der Gebrauchstauglichkeit (Usability), dem Benutzererlebnis (User Experience, UX) und „Arbeit 4.0“-Aspekten dar. Vorhandene Methoden des Software Engineering sind nicht geeignet, Beschäftigte angemessen in die Gestaltung und Entwicklung zu integrieren und Lösungskonzepte solcher Systeme auf Augenhöhe zu betrachten. In diesem Beitrag wird eine leichtgewichtige Canvas-Methode vorgestellt, die sich mit diesen Herausforderungen befasst. Sie umfasst die menschliche, die geschäftliche sowie die technologische Perspektive in einem gemeinsamen Kommunikationsinstrument, dem „Digital Assistance System Canvas“. Erste Evaluationen zeigen, dass die Teilnehmenden das Canvas-Konzept schätzen und die Methode vielseitig in verschiedenen Szenarien einsetzbar ist. Vielfältige Fragen in den Canvas-Bausteinen bereichern die gemeinsame Diskussion über neue Systeme und die Verbesserung bzw. Sicherstellung der Akzeptanz sowie die Denkweise in frühen Phasen des Design- und Entwicklungsprozesses.